2001
DOI: 10.1046/j.1469-7580.2001.19940393.x
|View full text |Cite
|
Sign up to set email alerts
|

The differential distribution of acetylated and detyrosinated alpha‐tubulin in the microtubular cytoskeleton and primary cilia of hyaline cartilage chondrocytes

Abstract: The primary cilium is a ubiquitous cytoplasmic organelle of unknown function. Ultrastructural evidence of primary cilia in chondrocytes, and their colocalisation with the Golgi apparatus, has led to speculation that these structures are functionally linked. To investigate the relationship between these organelles, we examined the molecular anatomy of the microtubular cytoskeleton in the chondrocytes of chick embryo sterna. Thick cryosections were immunolabelled with antibodies directed against acetylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 58 publications
5
111
0
Order By: Relevance
“…The assembly of primary cilia can also vary with culture conditions and the stage of the cell cycle (Tucker et al, 1979;Alieva et al, 1999). However, when the primary cilium is analyzed directly, this organelle colocalizes with the centrosome, and it is often in proximity to the Golgi apparatus (Poole et al, 1997(Poole et al, , 2001Aughsteen, 2001). Previous studies have shown that the DHC2/D2LIC complex localizes to the centrosomal region in mammalian tissue culture cells, where it overlaps with the position of the Golgi apparatus (Vaisberg et al, 1996;Grissom et al, 2002).…”
Section: Localization Of D2lic and Dhc2 In Mammalian Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assembly of primary cilia can also vary with culture conditions and the stage of the cell cycle (Tucker et al, 1979;Alieva et al, 1999). However, when the primary cilium is analyzed directly, this organelle colocalizes with the centrosome, and it is often in proximity to the Golgi apparatus (Poole et al, 1997(Poole et al, , 2001Aughsteen, 2001). Previous studies have shown that the DHC2/D2LIC complex localizes to the centrosomal region in mammalian tissue culture cells, where it overlaps with the position of the Golgi apparatus (Vaisberg et al, 1996;Grissom et al, 2002).…”
Section: Localization Of D2lic and Dhc2 In Mammalian Cellsmentioning
confidence: 99%
“…Perrone et al the primary function of the cDHC1b isoform is its role in flagellar assembly (Pazour et al, 1999;Porter et al, 1999;Wicks et al, 2000). Because the centrosomal region is also the site of assembly of the primary cilium (Wheatley et al, 1996;Poole et al, 1997Poole et al, , 2001, we reexamined the distribution of the complex in mammalian cells relative to sites of cilia assembly. Preliminary experiments with polarized cultures of MDCK cells indicated that D2LIC is present in a diffuse pattern throughout the apical cytoplasm (Figure 7, A and D).…”
Section: D2lic Colocalizes With Dhc2 At Sites Of Axoneme Assembly In mentioning
confidence: 99%
“…Polycystins-1 and -2 and many other proteins involved in cystogenesis are localized to the cilia, among other subcellular compartments (58). Several recent observations have begun to draw physical links between the cilia and the Golgi apparatus (47,59). For example, several proteins including IFT20, dyenin2, and kinesin-2 are found in both the Golgi apparatus and cilia (60).…”
Section: C-met and Hyperactivation Of Mtor Epithelial Cells Lining Cmentioning
confidence: 99%
“…One of the possible mechanisms would be modification of tubulin alpha chains. It was reported that chondrocyte primary cilium, structurally supported by microtubular cytoskeleton, plays important roles in obtaining environmental information from the extracellulr matrix of cartilage (28). Further, structural changes of cytoskeleton affect the viscoelastic properties of chondrocytes (34).…”
Section: Discussionmentioning
confidence: 99%